Transnational mothering, patterns and strategies of care-giving by Zimbabwean domestic workers in Botswana: a multi-sited approach - Takaindisa, Joyce (My University, 2020)
This thesis focuses on multi-sited transnational motherhood practices by examining the care triangle of transnational mothers who are single and working as domestic workers in Botswana, left-behind children and care-givers in Zimbabwe. Against a background that most studies on transnational parenting have tended to focus predominantly on the migrant’s experiences in the receiving context, usually centering on one player at a given time, this study fills in a gap by focusing on transnational family members in both the sending and receiving contexts. Through a multi-sited qualitative research approach in Botswana and Zimbabwe, data for this study was collected through a triangulation of data collection methods (narrative interviews, semi-structured interviews, solicited diaries and photography). Snowball and purposive sampling approaches were utilized. Conceptually, the study acknowledges the multiple-situatedness of migrants in more than one nation state. By so doing, the study filled in empirical, theoretical and methodological gaps in transnational parenting. Theoretically, the study is underpinned by transnational theory, global care chain theory, and new sociology of childhood studies, care circulation framework and intersectional theory. For data analysis, Interpretive Phenomenological Analysis (IPA) was used as the main analytic framework. This study brings Zimbabwe and Botswana into global discussions of transnational motherhood, mobility and care-giving in the era of heightened globalisation. The study also brings to the fore socially constructed underpinnings of motherhood and childhood against contested everyday realities of undocumented migrant mothers by offering new nuances beyond dominant ideologies. As such, the study rejects notions of the universal mother and universal child by privileging context and social location in understanding experiences of motherhood, caregiving and childhood in transnational families. The findings also expose transnational motherhood as a site of unequal power relations between, the state and extra- legal actors on one hand and migrant mothers on the other. The study therefore argues that state and non-state actors in the migration governance system of Botswana are central in the regulation of transnational families. The study highlights the role and contributions of the state and extra-legal actors in shaping the type of motherhood and indeed childhood that emerges in the context of undocumented migrant domestic workers in Botswana. It further illuminates participant’s struggles with difference as they strive to reconcile their personal circumstances in relation to dominant ideologies of motherhood and family. Even so, dominant discourses that privilege physical co-presence of biological mothers are further challenged as the findings also suggest that doing family does not necessarily mean doing so in a single physical location. Instead, this study acknowledges that doing family may mean family members are differentially located geographically and that some activities of fulfilling familial obligations like breadwinning may necessitate physical separation of family members in order for them to be fulfilled. Ultimately, though governed by dominant ideologies, motherhood can be altered by socio-economic demands of the transnational family. In relation to children, the study also challenges dominant constructions of a child as someone in constant need of care. Contrary to this notion, this study reveals that children are not only care-recipients but can also be care-givers in transnational family settings. Furthermore, dominant ideologies are also central in children’s perceptions of family but findings also suggest that children are capable of adjusting their thinking hence they accept maternal absence and migration when they can directly link the material benefits of their mother’s migration to their livelihoods. For the caregivers, findings also show that their care-giving is not given neutrally but is fraught with expectations of reciprocity for their future. Accordingly, by looking after left-behind children, they are in a way securing future social capital which they can draw from in their older ages. The narratives also indicate that caregivers, though widely regarded as other mothers in the absence of biological mothers do not fully embrace the role of mothers in its entirety. Contrarily, they are some roles that they designate as biological mother’s roles such as discipline. As such, findings suggest that caregivers may be reluctant to perform these roles but leave it for the absent mothers. Overall, findings from mothers, caregivers and left-behind children converge in the ways they all prescribe to hegemonic mothering suggesting their thinking is influenced by dominant ideologies of gender. Significantly, though maternal attitudes are driven by dominant ideologies, nonetheless, hegemonic ideologies remain malleable in response to mother’s socio-economic circumstances and location. Significantly, the study contributes to knowledge on transnational families in the context of the global South (South to South migration). Empirically, this study responds to the paucity of research in transnational motherhood in the Botswana context. Methodologically, by using a multi-sited approach, the contribution of this study lies in its recognition of transnational migrants as multiply situated beings whose activities permeate beyond the nation state thus doing away with methodological nationalism – the tendency to look at the nation state as the sole unit of analysis. By locating transnational family experiences from different geographical perspectives, this study contributes to a growing body of literature of transnational parenting using multi-sited approaches to the study of spatially disperses families
A thesis submitted to the Faculty of Humanities at the University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2020